Six-fold C–H borylation of hexa-peri-hexabenzocoronene - Nagase, Mai; Kato, Kenta; Yagi, Akiko; Segawa, Yasutomo; Itami, Kenichiro (Beilstein Journal of Organic Chemistry, 2020)
Hexa-peri-hexabenzocoronene (HBC) is known to be a poorly soluble polycyclic aromatic hydrocarbon for which direct functionalization methods have been very limited. Herein, the synthesis of hexaborylated HBC from unsubstituted HBC is described. Iridium-catalyzed six-fold C–H borylation of HBC was successfully achieved by screening solvents. The crystal structure of hexaborylated HBC was confirmed via X-ray crystallography. Optoelectronic properties of the thus-obtained hexaborylated HBC were analyzed with the support of density functional theory calculations. The spectra revealed a bathochromic shift of absorption bands compared with unsubstituted HBC under the effect of the σ-donation of boryl groups.
Keywords: C–H borylation; hexa-peri-hexabenzocoronene; iridium catalyst; X-ray crystallography

Polycyclic aromatic hydrocarbons - Harvey, R. G. (Wiley-VCH, 1997)

(untitled) - Narita, A.; Wang, X.-Y.; Feng, X.; Müllen, K. (Chem. Soc. Rev., 2015)

(untitled) - Wang, X.-Y.; Yao, X.; Müllen, K. (Sci. China: Chem., 2019)

(untitled) - Wu, J.; Pisula, W.; Müllen, K. (Chem. Rev., 2007)

(untitled) - Seyler, H.; Purushothaman, B.; Jones, D. J.; Holmes, A. B.; Wong, W. W. H. (Pure Appl. Chem., 2012)

(untitled) - Segawa, Y.; Maekawa, T.; Itami, K. (Angew. Chem., Int. Ed., 2015)

Large (C> = 24) Polycyclic Aromatic Hydrocarbons - Chemistry and Analysis - Fetzer, J. C. (Wiley Interscience, 2000)

(untitled) - Krieg, E.; Bastings, M. M. C.; Besenius, P.; Rybtchinski, B. (Chem. Rev., 2016)

(untitled) - Kokkin, D. L.; Troy, T. P.; Nakajima, M.; Nauta, K.; Varberg, T. D.; Metha, G. F.; Lucas, N. T.; Schmidt, T. W. (Astrophys. J., 2008)

(untitled) - Steglich, M.; Bouwman, J.; Huisken, F.; Henning, T. (Astrophys. J., 2011)

(untitled) - Hughes, J. M.; Hernandez, Y.; Aherne, D.; Doessel, L.; Müllen, K.; Moreton, B.; White, T. W.; Partridge, C.; Costantini, G.; Shmeliov, A.; Shannon, M.; Nicolosi, V.; et al. (J. Am. Chem. Soc., 2012)

(untitled) - Grzybowski, M.; Skonieczny, K.; Butenschön, H.; Gryko, D. T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Grzybowski, M.; Sadowski, B.; Butenschön, H.; Gryko, D. T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Dou, X.; Yang, X.; Bodwell, G. J.; Wagner, M.; Enkelmann, V.; Müllen, K. (Org. Lett., 2007)

(untitled) - Hartwig, J. F. (Acc. Chem. Res., 2012)

(untitled) - Tan, Y.-Z.; Yang, B.; Parvez, K.; Narita, A.; Osella, S.; Beljonne, D.; Feng, X.; Müllen, K. (Nat. Commun., 2013)

(untitled) - Cao, J.; Liu, Y.-M.; Jing, X.; Yin, J.; Li, J.; Xu, B.; Tan, Y.-Z.; Zheng, N. (J. Am. Chem. Soc., 2015)

(untitled) - Liu, Y.-M.; Hou, H.; Zhou, Y.-Z.; Zhao, X.-J.; Tang, C.; Tan, Y.-Z.; Müllen, K. (Nat. Commun., 2018)

(untitled) - Wu, J.; Fechtenkötter, A.; Gauss, J.; Watson, M. D.; Kastler, M.; Fechtenkötter, C.; Wagner, M.; Müllen, K. (J. Am. Chem. Soc., 2004)

(untitled) - Yamaguchi, R.; Hiroto, S.; Shinokubo, H. (Org. Lett., 2012)

(untitled) - Kato, K.; Lin, H.-A.; Kuwayama, M.; Nagase, M.; Segawa, Y.; Scott, L. T.; Itami, K. (Chem. Sci., 2019)

(untitled) - Ishiyama, T.; Murata, M.; Miyaura, N. (J. Org. Chem., 1995)

(untitled) - Kobayashi, K.; Kobayashi, N.; Ikuta, M.; Therrien, B.; Sakamoto, S.; Yamaguchi, K. (J. Org. Chem., 2005)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

Gaussian 16, Revision B.01 (Gaussian, Inc., 2016)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B: Condens. Matter Mater. Phys., 1988)